2021
DOI: 10.1002/ijgo.13526
|View full text |Cite
|
Sign up to set email alerts
|

Changing the landscape of obstetric resident education in low‐ and middle‐income countries using simulation‐based training

Abstract: Objective To evaluate simulation‐based training (SBT) in low‐ and‐middle‐income countries (LMIC) and the long‐term retention of knowledge and self‐efficacy. Methods We conducted an SBT course on the management of postpartum hemorrhage (PPH), shoulder dystocia (SD), and maternal cardiac arrest (MCA) in three government teaching hospitals in Guatemala. We evaluated changes in knowledge and self‐efficacy using a multiple‐choice questionnaire for 46 obstetrics/gynecology residents. A paired Student's t test was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…b "Attending" was translated from the Spanish word for "boss" ("jefe") by us (GO MOMS) [12] demonstrated that SBT was efficacious for use in training in low-resource settings by increasing short and long-term (> 6 month) clinical knowledge and self-efficacy regarding the management of obstetric emergences. In addition, others (PRONTO) have found that SBT can have an impact on local practice patterns, such as reducing the local incidence of cesarean sections [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…b "Attending" was translated from the Spanish word for "boss" ("jefe") by us (GO MOMS) [12] demonstrated that SBT was efficacious for use in training in low-resource settings by increasing short and long-term (> 6 month) clinical knowledge and self-efficacy regarding the management of obstetric emergences. In addition, others (PRONTO) have found that SBT can have an impact on local practice patterns, such as reducing the local incidence of cesarean sections [22].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have published studies [12] evaluating SBT in LMICs with a focus on short and longer-term retention of learning, however there is still a need to better understand the process of implementation and uptake of training into local practice cultures [13]. In order to better elucidate the long-term impact of SBT on obstetric emergencies, this study sought to provide an in-depth look at one institution's experience implementing SBT for the management of postpartum hemorrhage (PPH) in Guatemala.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we transitioned trainings into a traditional offsite 1-day session, which required a modified approach that compressed the training content, limited case-based discussions and reduced practical hands-on experience. Given simulation training along with group problem solving can be more effective at improving performance and knowledge, future traditional trainings will be better served if done over multiple days—or as initially planned over several months—to allow more time for these key complementary approaches 20 21. Based on our challenges facilitating a longer, more varied LDHF training approach, it will be important to monitor how a longer traditional training approach impacts provider participation and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings agree with those in the literature that B-Lynch suture and UBT are amenable to simulation training in resource-limited settings 20,21 . Prior work by us (GO MOMS) 12 demonstrated that SBT was e cacious for use in training in low-resource settings by increasing short and long term (> 6 month) clinical knowledge and self-e cacy regarding the management of obstetric emergences. In addition, others (PRONTO) have found that SBT can have an impact on local practice patterns, such as a reduction in the local incidence of C-Sect.…”
Section: Discussionmentioning
confidence: 99%